FAMILY FARMING IN THE CONTEXT OF GLOBAL CHALLENGES - Rositsa BELUHOVA-UZUNOVA; Krum HRISTOV; Mariyana SHISHKOVA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The current challenges related to the Covid-19 pandemic raise concern regarding security and sustainability of the global food system. As family farming plays a crucial role in the European agricultural sector, its support and development are vital to ensuring food sovereignty and security, including rural areas. It is the predominant farm model which accounts for more than 90% of the number of holdings and is considered as a main source of income and employment for rural population. In the context of global health crisis it is important to focus the attention on the issues and opportunities that family farms face. The aim of the study is based on an analysis of the observed trends in various aspects of family farming, to discuss the effects of Covid-19 and to highlight the strategies for the development of these agricultural production systems. The paper compares Bulgarian family farming with other EU member states. The survey indicates that although family farms dominate in the EU agricultural structure, they face number of challenges such as access to resources, financial aid, low competitiveness and investment activity.